Breaking the Silence : French Women's Voices from the Ghetto - Amara, Fadela (Book collections on Project MUSE., 2006)
Born in France of Algerian parents, Fadela Amara is a human rights activist who speaks with both a personal and a collective voice. This book is a passionate account of her struggle to found the movement called "Ni Putes Ni Soumises" (Neither Whore Nor Submissive), aimed at shattering the law of silence about violence against women within French suburban communities. The questions Amara raises are part of a broader agenda to open contemporary French society to greater ethnic and cultural diversity. These issues also pose problems of national identity and the defense of secularism for the state.